The Rockefeller Foundation and the experimental dimension in the campaign against hookworm disease in Colombia, 1920-1934 (2021)
This article analyses the treatment practices of the campaign against hookworm disease in Colombia, which was carried out through a cooperation agreement between the International Health Board (IHB) of the Rockefeller Foundation and the Colombian government between 1920 and 1934. Particularly, the processes that led to changes in treatment methods are analysed, as well as the variations in the doses of vermifuges and laxatives, that in many cases caused poisoning and deaths in the farmer population of the coffee region, which was the focal point of the campaign. The review of documentary sources, both local and international, on the campaign to fight hookworm disease in Colombia during the period 1920 and 1934, allowed for a reflection and understanding of how such treatment practices were part of an in situ experimental medicalisation process on the population, where the guidelines of time and cost directed, to a great extent, the decisions on what method and what treatment to follow.